2020
DOI: 10.1155/2020/3763069
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Circular RNAs in Regulating Adipogenesis of Mesenchymal Stem Cells

Abstract: The mesenchymal stem cells (MSCs) are known as highly plastic stem cells and can differentiate into specialized tissues such as adipose tissue, osseous tissue, muscle tissue, and nervous tissue. The differentiation of mesenchymal stem cells is very important in regenerative medicine. Their differentiation process is regulated by signaling pathways of epigenetic, transcriptional, and posttranscriptional levels. Circular RNA (circRNA), a class of noncoding RNAs generated from protein-coding genes, plays a pivota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 130 publications
(167 reference statements)
0
7
0
Order By: Relevance
“…Despite substantial research efforts aimed at characterizing the genetic regulation of obesity and adipogenesis, the molecular mechanisms underlying abdominal fat deposition remain largely unknown in mammals and economically important agricultural avian species, especially chickens. CircRNAs are ubiquitous across eukaryotes and have been increasingly implicated as master regulators of mammalian adipogenesis [ 41 , 42 ]. A number of circRNAs have been reported to share high evolutionary conservation among closely related species, even distantly related species [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite substantial research efforts aimed at characterizing the genetic regulation of obesity and adipogenesis, the molecular mechanisms underlying abdominal fat deposition remain largely unknown in mammals and economically important agricultural avian species, especially chickens. CircRNAs are ubiquitous across eukaryotes and have been increasingly implicated as master regulators of mammalian adipogenesis [ 41 , 42 ]. A number of circRNAs have been reported to share high evolutionary conservation among closely related species, even distantly related species [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adipose-derived stem cells (ASCs) are a population of mesenchymal stem cells with the multipotent capability in adipose tissue, which can be easily harvested during liposuction or resection of adipose tissue. A series of studies have demonstrated that ASCs can differentiate into many different cell types including osteocytes, chondrocytes, vascular endothelial cells, and adipocytes (Wang et al, 2020). ASCs have received considerable attention over the past decades, mainly because of their therapeutic potential in different areas of applied science.…”
Section: Regulation Mechanism Of Adipose-derived Stem Cells In Differ...mentioning
confidence: 99%
“…Adipogenesis is mainly divided into two stages: commitment and terminal differentiation. MSCs formed pre-adipocytes and then eventually differentiate into mature adipocytes ( Ambele et al, 2020 ; Wang F. et al, 2020 ). Specific detailed differentiation steps can be referred to the summary of our laboratory ( Wang F. et al, 2020 ).…”
Section: Mechanisms Of Adipogenic Differentiation Of Mesenchymal Stem Cellsmentioning
confidence: 99%